2023
DOI: 10.1002/pri.2015
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' experiences on assisting physiotherapy users during the COVID‐19 pandemic with lockdown measures in Spain

Helena Fernández‐Lago,
Carolina Climent‐Sanz,
Cristina Bravo
et al.

Abstract: BackgroundPhysiotherapists had faced a new healthcare scenario characterised by the restrictions caused by the COVID‐19 pandemic.PurposeTo explore the impact of the COVID‐19 pandemic on the physiotherapy profession from the perspective of physiotherapists working in the public and private sectors.MethodsQualitative study based on semi‐structured personal interviews with 16 physiotherapists working in public, private, or public‐private partnership sectors in Spain. The data were collected between March and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For example, our study found that people with low incomes visited the physiotherapist less than people with high incomes. This might be due to the saturation of the public health system and the limitation of paying for a private service [6]. Removing any inappropriate variation is necessary to improve the quality of physiotherapy care [27], and, for this, factors associated with not receiving physiotherapeutic care first need to be identified, as we have explored in the present study, in order to take steps in this regard and develop new strategies to improve access to this service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, our study found that people with low incomes visited the physiotherapist less than people with high incomes. This might be due to the saturation of the public health system and the limitation of paying for a private service [6]. Removing any inappropriate variation is necessary to improve the quality of physiotherapy care [27], and, for this, factors associated with not receiving physiotherapeutic care first need to be identified, as we have explored in the present study, in order to take steps in this regard and develop new strategies to improve access to this service.…”
Section: Discussionmentioning
confidence: 99%
“…The Spanish public health system has just over 5000 physiotherapists, a ratio of 0.1 per 1000 inhabitants, far below the recommendations of the World Health Organization (WHO) of 1 physiotherapist per 1000 inhabitants [5]. Approximately 90% of Spanish physiotherapists work in the private sector, representing a ratio of 0.9/1000 inhabitants [6]. The Spanish public physiotherapy service has long waiting lists, and private sector interventions are not refunded by the public system.…”
Section: Introductionmentioning
confidence: 99%